Training series and webinars on open & distance learning Faculty of Applied Sciences 2020 - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
The year 2020 is the year where all staff and students need to adapt to the dynamic Teaching & Learning strategies and skills of Open & Distance Learning or ODL. The faculty had taken several initial initiatives just before the first phase of the Movement Control Order (MCO) began at the end of March 2020 with a series of trainings for academic staff. This was done to provide initial preparation and exposure to all staff especially academic staff. During the MCO, additional series of trainings and webinars were organised on the sharing of experiences and best practices. As a result from these initiatives, an academic staff, Shamsul Bahrin Gulam Ali, received the ODL UiTM 2020 Award during the University Academic Awards 2019.